2011
DOI: 10.1007/s12070-010-0103-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Audio-Rhinological Changes During Pregnancy

Abstract: A number of physiological changes occur during pregnancy and amongst them, audiological and nasal changes are quite significant. These are mainly due to the changing levels of sex hormones and return to normal once the pregnancy is over. This study was conducted to document these changes. Forty (pregnant 40 and non-pregnant 40) consenting subjects in age group of 20-35 years were assigned to test and control groups. They underwent complete ENT and Obstetric examination. In test group Pure Tone Audiometry was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 12 publications
1
20
0
6
Order By: Relevance
“…16 • This study assessed oestrogen, progesterone, growth hormone and insulin-like growth factor 1 in pregnant Malaysian women with and without rhinitis • Rhinitis occurred in 53.3 per cent of women • There was a trend towards raised oestrogen and insulin-like growth factor 1 in the rhinitis group • Significantly more rhinitis patients had female babies Female babies were more common among patients with pregnancy rhinitis: 14 of the 16 rhinitis group patients had female babies, compared with 7 of the 14 non-rhinitis group patients ( p = 0.003).…”
Section: Discussionmentioning
confidence: 99%
“…16 • This study assessed oestrogen, progesterone, growth hormone and insulin-like growth factor 1 in pregnant Malaysian women with and without rhinitis • Rhinitis occurred in 53.3 per cent of women • There was a trend towards raised oestrogen and insulin-like growth factor 1 in the rhinitis group • Significantly more rhinitis patients had female babies Female babies were more common among patients with pregnancy rhinitis: 14 of the 16 rhinitis group patients had female babies, compared with 7 of the 14 non-rhinitis group patients ( p = 0.003).…”
Section: Discussionmentioning
confidence: 99%
“…Maternal and fetal safety should be privileged, using those medications with proven safety. que pueden afectar la audición y producir cambios rinosinusales importantes 5 . Cambios fisiológicos en el oído: existe evidencia sobre la existencia de receptores de estrógenos en las vías auditivas y en las regiones de regulación hidroelectrolítica auditiva 6 .…”
Section: Cambios Fisiológicos Durante El Embarazounclassified
“…Cambios fisiológicos en el oído: existe evidencia sobre la existencia de receptores de estrógenos en las vías auditivas y en las regiones de regulación hidroelectrolítica auditiva 6 . En el embarazo se puede producir un descenso gradual en la agudeza auditiva en las frecuencias graves (125, 250, 500 y 1.000 Hz), sin llegar a conformar una hipoacusia patológica, que retorna a la normalidad en el periodo posparto 5 . Además, durante el embarazo se pueden deteriorar patologías preexistentes como la otoesclerosis y la enfermedad de Ménière 6 .…”
Section: Cambios Fisiológicos Durante El Embarazounclassified
“…5 Tandon et al and Sharma et al in 2 separate studies observed that normal pregnancy has some depressant effect on the auditory conduction pathway and these observations were based on a study conducted on a group of pregnant women. 6,13 In 2001, Stenberg et al tried mapping the estrogen receptors (ERs) in the human inner ear and found ERa to be present in the spiral ganglion and ERb in the stria vascularis, both of the locations being important in auditory conductive pathway. 14 Kilicdag et al observed that postmenopausal women in normal population have better hearing with administered estrogen replacement therapy and suggested a possible protective effect of estrogen on hearing function.…”
Section: Introductionmentioning
confidence: 99%